Production of a carrier-free standard 56Mn source for the NRC manganese salt bath. (December 2019) - Galea, R.; Moore, K.
Abstract: The National Research Council (NRC) of Canada's primary method for emission rate for radionuclide neutron sources utilizes a manganese salt bath which was last calibrated in the 1960s. At that time, an NRC RaBe neutron source was used to irradiate a solution of calcium permanganate to take advantage of the Szilard-Chalmers effect in producing the bulk 56 Mn material for standardization and calibration of the bath. When attempting to repeat this exercise, a small amount ( 100 kBq) was produced. This amount was sufficient for the standardization process but did not yield enough material to calibrate the bath to a sufficient level of precision. Improvements upon the previous separation scheme adopted at NRC for the separation of the 56 Mn from the bulk irradiated material included the rinsing of the 56 Mn dioxide precipitate using a mixture of sulfuric acid and hydrogen peroxide. While these improvements made in the separation chemistry improved the yield of 56 Mn extraction from 60% to above 95% the maximum amount of activity was still quite low. Hence in March of 2018, the SLOWPOKE-2 Facility at the Royal Military College in Kingston, ON, was used to irradiate three vials of KMnO4 in solution. An estimated 2 GBq was produced and sent to NRC, from which the extraction procedure recovered essentially all of the available 56 Mn. The 56 Mn was standardized using the 4 π β − γ anti-coincidence counting system and confirmed using the CIEMAT/NIST primary method. The resulting bulk material was certified with an uncertainty of 0.8% (k = 2). Minor quantities of 65 Zn, 69m Zn and 42 K were unexpectedly observed but were in minute quantities so as not to affect the results of the standardization or calibration. The standardized 56 Mn artifact was used to calibrate the Secondary Standard Ionizing Radiation Chamber System (SSIRCS) for a more rapid deployment of the calibrant in the future. Highlights: The NRC primary standard for neutron emission rate, the Manganese salt bath was calibrated. The Szilard-Chalmers effect, along with an improved purification scheme produced a pure 56 Mn bulk source for standardization. The resulting calibration recovered the neutron emission rates of traceable sealed neutron sources at NRC.